Propuesta de un programa físico recreativo para mejorar la calidad de vida en el adulto mayor de 65 años de edad - Rodas Mena, Diego Javier (2016)
This research entitled: PROPOSAL OF A RECREATIONAL PHYSICAL PROGRAM TO IMPROVE THE QUALITY OF LIFE IN ADULTS ELDERLY OVER 65 YEARS OF AGE. It focuses on the related problem in: How to design a physical-recreational program to improve the quality of life of the older adult at age 65 in the Central District of the City of Francisco de Orellana? The general objective was: To design a recreational physical program to improve the quality of life in adults over 65 years of age in the Central District of the city of Francisco de Orellana. During the investigation, theoretical methods such as analysis-synthesis, induction-deduction, hypothetico-deductive, among the empirical methods were used: observation, surveys, document review and description, which allowed us to achieve the objectives And mapped tasks. The sample selected was the following: 5 teachers 40 seniors. The results obtained show an improvement in the quality of life of the participants in this program, analyzed by the pathologies that were detected before starting the program among which we mention arterial hypertension, diabetes, bronchial asthma, Osteoarthritis, decreased physical capacity.